2020
DOI: 10.18203/2320-6012.ijrms20204867
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of electronic medical records system among frontline health care workers in Jos University teaching hospital, Plateau State Nigeria

Abstract: Background: Electronic Medical Records system (EMRs) in any healthcare system has the potential to transform healthcare in terms of saving costs, reducing medical errors, improving service quality, increasing patients’ safety, decision-making, saving time, data confidentiality, and sharing medical. Evidence on the current state of EMR system in Nigeria health system particularly its knowledge among health professionals is limited. Hence, this study was conducted to assess the level of knowledge EMRs among fron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…Another possible explanation for this result was that they might be more aware of the challenges of paper-based medical record system such as lack of storage space, medical errors, patient's safety and data confidentiality. A study carried out among the healthcare workers in Nigeria reported that the duration of services was not associated with the knowledge on EMRs [35].…”
Section: Plos Onementioning
confidence: 97%
“…Another possible explanation for this result was that they might be more aware of the challenges of paper-based medical record system such as lack of storage space, medical errors, patient's safety and data confidentiality. A study carried out among the healthcare workers in Nigeria reported that the duration of services was not associated with the knowledge on EMRs [35].…”
Section: Plos Onementioning
confidence: 97%
“…Since those who know telemedicine well might not necessarily know the whole of HITs', there might be a gap in the overall knowledge levels. Similarly, a 2020 study in the Plateau State of Nigeria found that 71.5% of health professionals who worked at the frontline had good level of knowledge [ 27 ]. This is supported by a 2016 study among health professionals working at teaching hospitals in Puducherry Union Territory, India, which found that 41% had good level of knowledge which is higher than the current study's finding [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study adopted a mixed-method research approach using qualitative and quantitative measures to determine barriers in digitizing health information in Kenya and Lao PDR heuristically [17,18]. According to the methodology applied in previous studies, we heuristically identified the barriers or obstacles for digitalizing health information from qualitative data analyses of in-depth interviews; then, we quantitatively validated the identified issues and detected additional other issues that could not be identified by qualitative analyses using registered data in parallel [19][20][21][22][23].…”
Section: Methodsmentioning
confidence: 99%